Doing Counseling Online: Is It Effective For Farmers? - Lakatara, Rima; Halid, Amir (Universitas Negeri Gorontalo, 2023)
The current online-based era is part of advanced technology powered by the internet and has brought many changes in result. This study aimed to discern how online-based counseling communication has developed in farmer groups, and determine the effect of online-based counseling communication improvement on the work volume of farmer groups. This research conducted from September 2021 to March 2022 in Telaga Subdistrict, Gorontalo Regency. Simple random sampling was used to collect the data and determined by Slovin formula. Data were analyzed using multiple linear regression analysis techniques, and hypothesis testing was carried out. The results of the study revealed that The right person, and The right communication tools partially had a positive and significant influence on the effectiveness of online-based counseling. This study found that location constraints were not a problem in online-based counseling activities, but extension support and the communication tools used greatly determined the effectiveness of online-based counseling.